Cognition differentiates gait speed among older adults. (31st December 2021) - Paulson, Sally; Gray, Michelle; Glenn, Jordan M.; Madero, Erica N.; Myers, Jennifer; Gills, Joshua L.; Jones, Megan; Campitelli, Anthony; Vincenzo, Jennifer; Walter, Christopher
Abstract: Background: The ability to perform a motor and cognitive dual‐task (DT) becomes more challenging as one ages and shows a greater deficit, if one has a cognitive impairment (CI). CI has also been shown to predict a decline in physical functioning. Therefore, the purpose was to examine differences between cognitively healthy (CN) and cognitively impaired (CI) older adults on gait speed (GS) during habitual (HAB) and fast (FAST) walking trials with and without a DT. Method: 83 older adults (80.66±5.36) completed a digital Visual Paired Comparison (VPC) cognitive assessment, which measured working memory, and a Digital Symbol (DS) cognitive assessment, which measured processing speed. Participants were grouped into CN or CI based on their results for each assessment. Subjects performed two trials of each walking test: HAB, FAST, HAB‐DT, and FAST‐DT. The DT trials were performed using a working memory task. GS was calculated using the time to cover 10m. One‐way ANOVA was used to assess for differences in GS between VPC and DS cognitive groups. Result: While HAB GS (p=.10) was not significantly different between the VPC cognitive groups, the CN group walked significantly faster than the CI group during the FAST, HAB DT, and FAST DT trials (p<.05). There was not a significant difference in HAB GS (p=.10) or HAB DT GS (p=.08) between the CI and CN DS groups. However, the DS CI group walked significantly slower during the FAST (p=.03) and FAST DT (p=.05) assessments. Conclusion: Individuals with CI showed no statistical difference in habitual walking speed. However, this was clinically meaningful as the individuals with an average or above average working memory and processing speed walked faster than individuals with CI by 8.4% and 6.5%, respectively. While GS declined during the DT trials, individuals with a working memory impairment showed a greater decline, and it was even larger during the fast DT trials and for individuals with a working memory (19.5%) or processing speed (17.6%) impairment. Previous research has suggested DT walking involves activation of the prefrontal cortex, which may partially explain the greater decline in DT GS for those with working memory impairment.